Beta-Adrenergic Antagonist Tolerance in Amyloid Cardiomyopathy - Ramsell, Stuart; Arias Bermudez, Carlos; Takem Baiyee, Cyril Ayuk Mbeng; Rodgers, Brandon; Parikh, Samir; Almaani, Salem; Sharma, Nidhi; LoRusso, Samantha; Freimer, Miriam; Redder, Elyse; Bumma, Naresh; Vallkati, Ajay; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Beta-adrenergic antagonists or blockers (BB) are a cornerstone of cardiac therapy for multiple indications. However, BB are considered relatively contraindicated in amyloid cardiomyopathy due to poor tolerance. This intolerance is hypothesized to be due to concomitant neuropathy and significant restrictive cardiomyopathy. This study analyzes the incidence and characteristics of BB tolerance in patients with amyloid cardiomyopathy. Methods: Through a single-center retrospective chart review, patients with amyloid cardiomyopathy, confirmed by endomyocardial biopsy or technetium-99 pyrophosphate scan, were identified and clinical data was collected. Statistical methods included Chi-square test and two sample t-tests. Results: Of 135 cardiac amyloidosis patients, 27 patients (20.0%) had no BB use, 56 patients (41.5%) were current BB users, and 52 patients (38.5%) were prior BB users. The most frequent indications for BB use were heart failure, hypertension, coronary artery disease, and arrhythmia. The most common reason for stopping BB therapy was hypotension (62.8%) followed by fatigue, bradycardia, and orthostasis. Neurologic symptoms at the initial BB prescription or most recent evaluation were not significantly difference between current and prior BB users. Their cardiovascular profiles were similar by ejection fraction, wall thickness, troponin I, and brain natriuretic peptide. There was no association for BB discontinuation based on amyloid subtype, sex, or race. Conclusion: The majority of patients with amyloid cardiomyopathy were prescribed BB, and over half of these patients still tolerated BB therapy. Current and prior BB users had similar profiles from a cardiovascular and neurologic perspective, with no association identified to predict BB discontinuation.